Microbial Community and Metabolite Dynamics During Soy Sauce Koji Making - Tan, Guiliang; Hu, Min; Li, Xiangli; Li, Xueyan; Pan, Ziqiang; Li, Mei; Li, Lin; Wang, Yi; Zheng, Ziyi (Frontiers in Microbiology, 2022)
Koji making is a pre-fermentation stage in soy sauce manufacturing that impacts final product quality. Previous studies have provided valuable insights into the microbial species present in koji. However, changes in microbial community functional potential during koji-making are not well known, nor are the associations among microbial populations and flavoring characteristics. In the present study, we investigated the succession of microbial communities, microbial community functional potential, metabolite profiles, and associations among microbial community members/functions with metabolites during koji making using shotgun metagenomic and metabolomic analyses. Firmicutes, Proteobacteria, and Ascomycota were identified as the most abundant microbial phyla in early koji making (0–12 h). Aspergillus (fungi) and Weissella (bacteria) exhibited marked abundance increases (0.98% to 38.45% and 0.31% to 30.41%, respectively) after 48 h of fermentation. Metabolite analysis revealed that aspartic acid, lysine, methyl acetate, isovaleraldehyde, and isoamyl alcohol concentrations increased ~7-, 9-, 5-, 49-, and 10-fold after 48 h of fermentation. Metagenomic profiling demonstrated that koji communities were dominated by genes related to carbohydrate metabolism and amino acid metabolism, but functional profiles exhibited marked shifts after 24 h of fermentation. The abundances of genes within the categories of carbohydrate and amino acid metabolism all increased during koji making, except for pyruvate metabolism, glycolysis/gluconeogenesis, and the citrate cycle. Correlational analyses indicated that Aspergillus, Lactococcus, Enterococcus, Corynebacterium, and Kocuria abundances were positively correlated with 15 amino acid concentrations (all p < 0.05), while Weissella abundances were positively correlated with concentrations of volatile flavor compounds, including eight amino acids, phenylacetaldehyde, acetic acid, 2,3-butanediol, ethyl acetate, and ethanol (p < 0.05). These results provide valuable information for understanding the microbial-associated mechanisms of flavor formation during koji making.